The Experiences of Practice Educator Facilitators and Academics Supporting Adult Nursing Students Completing a Paid Placement During the COVID-19. (2022) - Cushen-Brewstera, Noreen; Barkera, Annie; Driscoll-Evans, Paul
No abstract available